Adapting New Testing Methods to the Tangent Screen - Pace, R (Canadian Journal of Optometry, 1983)
Tangent screen examination has remained a popular method for detecting visual field defects in spite of the recent availability of more sophisticated perimetric instrumentation. Many techniques used with these newer instruments can be adapted for use with the tangent screen in order to enhance its sensitivity in detecting early field problems. Some of these techniques, including the glaucoma screening method of Armaly and Drance, are discussed with this emphasis.